Compressive and tensile bending of sputter deposited Al/Mo bilayers. (15th March 2019) - Kreiml, Patrice; Rausch, Martin; Terziyska, Velislava L.; Winkler, Jörg; Mitterer, Christian; Cordill, Megan J.
Abstract: Cyclic bending tests of magnetron sputter-deposited Al/Mo bilayer thin films on flexible substrates were performed with a custom-built bending apparatus to evaluate the reliability of possible applications for metal wiring electrodes such as signal and data bus lines in flexible electronics. Intermittent measurements of mechanical damage and electrical resistance were performed to elucidate the damage evolution of Al/Mo bilayers with increasing cycle numbers. It was found that a 3:1 thickness ratio would have an extremely long lifetime when only compressive bending is applied for strains <1.3% (2 mm radius, 50 μm substrate thickness). Graphical abstract: Unlabelled Image